Juvenile Osteochondral Lesions of the Talus: Current Concepts Review and an Update on the Literature - Albert T. Anastasio; Kian Bagheri; Emily M. Peairs; Caitlin Grant; Samuel B. Adams (MDPI AG, 2023)
Osteochondral lesions of the talus (OLTs) are lesions that occur before the physis closes and are frequently associated with acute ankle trauma. These lesions are often difficult to diagnose due to swelling and inflammation that are present after the initial injury. A growing body of literature has assessed the effects of OLTs in the adult population. However, the literature examining these lesions in the juvenile population is sparse. The purpose of this review is to provide a thorough understanding of OLTs, with a specific focus on the juvenile population. We evaluate the recent literature regarding the outcomes of various surgical treatment; modalities in the pediatric patient. While the outcomes after surgical treatment of pediatric OLTs are generally favorable, the paucity of investigation in this demographic is alarming. Further research is needed to better inform practitioners and families regarding these outcomes, as treatment plans are highly dependent on the individual patient in question.